Application of a nomogram model for the prediction of 90-day poor outcomes following mechanical thrombectomy in patients with acute anterior circulation large-vessel occlusion - Li, Xia; Li, Chen; Liu, Ao-fei; Jiang, Chang-chun; Zhang, Yi-qun; Liu, Yun-e; Zhang, Ying-ying; Li, Hao-yang; Jiang, Wei-jian; Lv, Jin (Frontiers in Neurology, 2024)
The past decade has witnessed the advancement in mechanical thrombectomy (MT) for acute large-vessel occlusions (LVOs). However, only approximately half of the patients with LVO undergoing MT show the best/independent 90-day favorable outcome. This study aimed to develop a nomogram for predicting 90day poor outcomes in patients with LVO treated with MT.Methods A total of 187 patients who received MT were retrospectively analyzed. Factors associated with 90-day poor outcomes (defined as mRS of 4-6) were determined by univariate and multivariate logistic regressions. One best-fit nomogram was established to predict the risk of a 90-day poor outcome, and a concordance index was utilized to evaluate the performance of the model. An additional 145 patients from a single stroke center were retrospectively recruited as the validation cohort to test the newly established nomogram. Results The overall incidence of 90-day poor outcomes was 45.16% (84/186) in the training set. Five variables, namely, age (odds ration [OR]: 1.049, 95% CI [1.016-1.083]; P = 0.003), glucose level (OR: 1.163, 95% CI [1.038-1.303]; P = 0.009), baseline National Institute of Health Stroke Scale (NIHSS) score (OR: 1.066, 95% CI [0.995-1.142]; P = 0.069), un-successful recanalization (defined as a TICI grade of 0 to 2a) (OR: 3.730, 95% CI [1.688-8.245]; P = 0.001), and early neurological deterioration (END, defined as an increase of ≥ 4 points between baseline NIHSS score and the NIHSS score at 24 hours after MT) (OR: 3.383, 95% CI [1.411-8.106]; P = 0.006) were included in the nomogram to predict the potential risk of poor outcomes at 90-d 4 following MT in LVO patients, with a C-index of 0.763 (0.693-0.832) in the training set and 0.804 (0.719-0.889) in the validation set, respectively. Conclusion The proposed nomogram provided clinical evidence for effective control of these risk factors before or during the processes of MT surgery in LVO patients.